1984
DOI: 10.1037/0012-1649.20.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Infants' manipulative exploration of objects: Effects of age and object characteristics.

Abstract: The research reported here was supported by Grant HD 11916 from the National Institute of Child Health and Human Development.The author is grateful to Katharine Lawson and Gerald Turkewitz for their helpful comments on a previous draft and to Mary Capozzoh, Karen Cumbus, and Phyllis Klein for their patient help in scoring videotapes and organizing data Requests for reprints should be sent to Holly A. Ruff, Room 222

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
266
0
5

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 325 publications
(291 citation statements)
references
References 24 publications
20
266
0
5
Order By: Relevance
“…Therefore, we focused on age, without relying on gender, to explain hand-to -mouth activity. This result corresponds with data reported by Ruff (1984), Ruff and Dubiner (1987) and Groot et al (1998) who showed that there is no statistically significant difference in mouthing events between boys and girls. There is, however, a significant relationship between mouthing and age of the child.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, we focused on age, without relying on gender, to explain hand-to -mouth activity. This result corresponds with data reported by Ruff (1984), Ruff and Dubiner (1987) and Groot et al (1998) who showed that there is no statistically significant difference in mouthing events between boys and girls. There is, however, a significant relationship between mouthing and age of the child.…”
Section: Resultssupporting
confidence: 92%
“…Mouthing behavior develops into an exploratory behavior in which objects are placed into the mouth for a few seconds for purposes of discovery. During this stage of development, children will put their hands and any object that they come in contact with into their mouths (Ruff, 1984;Ruff and Dubiner, 1987;Davis et al, 1995;Groot et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They recognize affordances of objects and tailor their actions accordingly (Clifton, Rochat, Litovsky, & Perris, 1991;Lockman, Ashmead, & Bushnell, 1984;McCarty, Clifton, Ashmead, Lee, & Goubet,, 2001;von Hofsten & Ronnqvist, 1988;von Hofsten & Fazel-Zandy, 1984). In addition, young infants detect the functional relation between object parts and surfaces and use objects in ways that are consistent with these relations (Bourgeois, Khawar, Neal, & Lockman, 2005;Gibson & Walker, 1984;Molina & Jouen, 1998;Palmer, 1989;Ruff, 1984). Infants 8 to 18 months of age manipulate objects on the basis of the functions they afford (Freeman, Lloyd, & Sinha, 1980;Pier-LeBonniec, 1985), generalize functional properties to objects similar in appearance or that share important characteristics (Baldwin, Markman, & Melartin, 1993;Booth & Waxman, 2002a), and attend to novel ways objects can be used and imitate those actions (Meltzoff, 1988a,b).…”
Section: Increasing Infants' Sensitivity To Color By Making Color Funmentioning
confidence: 99%
“…Aos quatro meses de idade são capazes de perceber propriedades de rigidez (ROCHAT, 1983), aos 6 meses percebem temperatura (BUSHNELL; WEINBERGER; SASSEVILLE, 1989), peso (MOUNOUD; BOWER, 1974;PALMER, 1989;RUFF, 1984) e forma (BRYANT et al, 1972). A maioria destes estudos usaram uma ou mais das seguintes variáveis para suas inferências: pressão exercida pelo aperto, frequência do aperto e tempo (duração) dos apertos.…”
Section: Preensão Ativaunclassified